2015
DOI: 10.5009/gnl14120
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab versus Cyclosporine Treatment for Severe Corticosteroid-Refractory Ulcerative Colitis: A Korean, Retrospective, Single Center Study

Abstract: Background/AimsIn patients with corticosteroid-refractory ulcerative colitis (UC), cyclosporine or infliximab may be added to the treatment regimen to induce remission. Here, we aimed to compare the efficacy of cyclosporine and infliximab.MethodsBetween January 1995 and May 2012, the medical records of 43 patients with corticosteroid-refractory UC who received either infliximab or cyclosporine as a rescue therapy at a tertiary care hospital in Korea were reviewed.ResultsAmong the 43 patients, 10 underwent resc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…The studies were published between 2004 and 2018 and the follow-up period ranged at least from 1 year to maximum of 10 years. In the quantitative analysis, we used data from three RCTs (13,18,19) and 12 cohort studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). A total number of 1,607 patients with steroid-refractory ASUC were included, 879 of which (54.7%) were treated with CYS and the other 728 (45.3%) with IFX.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were published between 2004 and 2018 and the follow-up period ranged at least from 1 year to maximum of 10 years. In the quantitative analysis, we used data from three RCTs (13,18,19) and 12 cohort studies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). A total number of 1,607 patients with steroid-refractory ASUC were included, 879 of which (54.7%) were treated with CYS and the other 728 (45.3%) with IFX.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…Only two studies reported a single infusion of IFX (20,30). In the IFX treatment groups, AZA was the most commonly administered maintenance drug, albeit recent studies continued IFX (13,23,24,26,28). Due to the lack of available safety data during long-term follow-up in an RCT, the CYSIF trial (18), AE and SAE results reported in the original study were used in the meta-analysis (12).…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…However, infliximab with azathioprine may be more effective than ciclosporin alone to avoid colectomy [25]. Table 2 compares the results of our study with those of a recent Spanish study done in 2016 involving 62 patients with severe acute colitis [26]; it shows a high rate of colectomy in our series compared to the Spanish series, and this is due to the unsatisfactory availability of second-line medical treatment which impose us to recourse to colectomy frequently ( Table 2).…”
Section: Monterubbianesi Et Al Reported In a Study Involving 113 Patmentioning
confidence: 40%
“…While no difference was found between the treatments in preventing colectomy, infliximab with azathioprine seemed to be superior to cyclosporine monotherapy when it comes to preventing colectomy. 7 Overall therapeutic response rates of infliximab in Asian IBD patients appeared to be similar or higher than those in patients from Western countries.…”
Section: Introductionmentioning
confidence: 99%